Penerapan Model Pembelajaran Kuantum (Quantum Teaching) Untuk Meningkatkan Hasil Belajar Sistem Perkembangbiakan Tumbuhan Dan Hewan Peserta Didik Kelas IX-7 MTsN 2 Kota Bima - Siti Nuraini (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
Learning and learning outcomes on the material of plant and animal breeding systems through a quantum learning model (quantum teaching) in Class XI-7 MTsN 2 Bima City. The method used is classroom action research (Classroom Action Research). This classroom action research procedure is designed for 2 (two) cycles. Each cycle is carried out according to the changes achieved as stated in the investigated factors. The types of data in this research are lesson plans, science learning test results, observation results, and interview results sourced from students, teachers, and documents in the teaching and learning process. The conclusions of this study indicate (a) learning using a quantum teaching strategy affects the effectiveness of the learning process in the classroom; (b) Students are very enthusiastic and motivated to take part in science lessons on plant and animal breeding systems with increased activity in RPP cycle I and cycle II; (c) Student learning outcomes increased with the average value of students in the first cycle was 78.88 to 84.97 in the second cycle; and (d) students' classical mastery increased in the first cycle from 68.57% to 82.85% in the second cycle.